Predictors of Weight Loss in Obese Older Adults: Findings from the USA and the UK - Sarah E. Jackson; Rebecca J. Beeken; Jane Wardle (Obesity Facts, 2014)
Objective: To examine the prevalence and demographic predictors of clinically meaningful weight loss in community samples of obese older adults in the USA and the UK. Methods: Data were from obese older adults (BMI ≥ 30 kg/m2; age ≥ 52 years), free of a cancer diagnosis, from the Health and Retirement Study (HRS; n = 3398) and the English Longitudinal Study of Ageing (ELSA; n = 998). Weight change was assessed from 2004 to 2008. Multivariable logistic regression tested whether age, sex, ethnicity, marital status, education, or BMI predicted ≥ 5% weight loss. Results: Over a quarter (28.7%) of obese participants from HRS and 16.6% from ELSA lost ≥ 5% weight. Being female (odds ratio (OR) = 1.31, 95% confidence interval (CI) = 1.11-1.54) and heavier (BMI ≥ 35 kg/m2) (OR = 1.60, 95% CI = 1.37-1.87) predicted weight loss in HRS. Trends were similar in ELSA (female: OR = 1.18, 95% CI = 0.83-1.69; BMI ≥ 35 kg/m2: OR = 1.24, 95% CI = 0.85-1.82). ORs were increased in ≥ 65-year-olds in HRS (OR = 1.55, 95% CI = 1.33-1.81), and reduced in married people in ELSA (OR = 0.69, 95% CI = 0.48-1.00). Neither education nor ethnicity predicted weight loss in either cohort. Conclusion: A high proportion of obese older adults experience clinically meaningful weight loss, but few demographic variables consistently predict weight loss in this population.